Enhanced Cell Response to Zirconia Surface Immobilized with Type I Collagen. (May 2019) - Hsu, C.M.; Sun, Y.S.; Huang, H.H.
Zirconia (ZrO2 ) dental implants provide good biocompatibility, have good corrosion resistance, and have a color that is similar to that of natural teeth. Unfortunately, ZrO2 is a bioinert material and therefore achieves osseointegration difficultly. In this study, we sought to enhance osseointegration by producing rough ZrO2 surfaces that contain hydroxyl groups (designated ZSA) through the use of sandblasting in conjunction with alkaline treatment. We immobilized type I collagen on ZSA surfaces using the natural cross-linker, procyanidin. Our results further showed that surfaces produced in ZSA-P/C featured more and steadier type I collagen than surfaces produced in ZSA-C. The ZSA-P/C also presented superior cell responses in terms of adhesion, proliferation, and mineralization of human bone marrow mesenchymal stem cells. The enhanced cell responses in the ZSA-P/C were induced through the prolonged activation of focal adhesion kinase, AKT (the phosphoinositide 3-kinase pathway), and p38 (the mitogen-activated protein kinase pathway). The simple and novel approach to immobilize type I collagen on roughened ZrO2 surfaces presented in this article can likely benefit dental implant applications.